Uncovering the mechanism of resveratrol in the treatment of asthma: a network pharmacology approach with molecular docking and experimental validation - Li Chunxiao; Hou Xin; Liu Bowen; Sun Bingqing; Zhou Mengqi; Zhang Shuwen; Zhang Jingyuan; Lin Jiangtao (Frontiers in Pharmacology)
BackgroundEvidence for the benefits of resveratrol (Res) in the treatment of asthma is progressively accumulating. However, the full spectrum of its molecular targets and the precise mechanisms remain incompletely characterized.MethodTargets of Res were obtained from Swiss Target Prediction, TCMCP, and DrugBank. Targets of asthma were obtained from DisGeNET, Therapeutic Target Database, GeneCards, and DrugBank. Intersecting target genes were identified by using jvenn. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomics (KEGG) enrichment analyses were performed using the R package clusterProfiler in R version 4.4.0. Protein–protein interaction networks were constructed using Cytoscape 3.9.1 software. Molecular docking validation of the binding capacity between Res and targets was performed using AutoDock Vina and visualized in PyMOL version 3.0.4. ELISA and Western blotting were used to verify the reliability of Res effects on the top five targets in both house dust mite (HDM)-induced asthma mouse model and BEAS-2B cell model.ResultsAfter the intersection of the 236 Res targets and the 2,382 asthma targets, 120 targets for Res against asthma were obtained. The top five therapeutic targets based on weighted degree score were TNF, IL6, STAT3, TP53, and IL1B. GO enrichment analysis identified 2,595 significant terms, associated with 2,402 biological processes, followed by 153 molecular functions and 40 cellular components. KEGG enrichment analysis identified 107 relevant pathways, including “apoptosis,” “TNF signaling pathway,” and “MAPK signaling pathway.” Molecular docking showed that Res had a strong binding affinity toward the top five targets with binding energies less than −5.8 kcal/mol. Res treatment normalized the dysregulated expression of TNF-α, IL-6, STAT3, p53, and IL-1β both in vitro and in vivo.ConclusionRes may target TNF-α, IL-6, STAT3, p53, and IL-1β to act as a therapeutic agent for asthma. These findings reveal the potential therapeutic targets for Res against asthma and provide theoretical bases for the clinical application of Res.